2022
DOI: 10.3325/cmj.2022.63.148
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-melanoma skin cancer development in renal transplant recipients: a 40-year retrospective study in Croatia

Abstract: Aim To determine the prevalence of non-melanoma skin cancer (NMSC) and disease-specific risk factors in renal transplant recipients (RTRs). Methods This retrospective cohort study enrolled 1232 RTRs (736 men) treated in University Hospital Center Zagreb over 40 years. The effect of sex, age at transplantation, geographic residence, dialysis vintage, and the type of immunosuppressive therapy on NMSC occurrence was investigated. Results The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…Our results showed that 23% of patients diagnosed with NMSC were within the first 5 years after transplantation, while 51.3% had been transplanted for over 10 years. Advanced age has been identified in the literature as a risk factor for NMSC development in RTx [19,20]. We found that the average age of RTxs at the time of NMSC diagnosis was significantly higher compared to RTx without this type of cancer, increasing the risk of developing this tumor by more than 5 times, consistent with other research in individuals with the same clinical condition [14,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that 23% of patients diagnosed with NMSC were within the first 5 years after transplantation, while 51.3% had been transplanted for over 10 years. Advanced age has been identified in the literature as a risk factor for NMSC development in RTx [19,20]. We found that the average age of RTxs at the time of NMSC diagnosis was significantly higher compared to RTx without this type of cancer, increasing the risk of developing this tumor by more than 5 times, consistent with other research in individuals with the same clinical condition [14,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Organ transplant recipients face a significantly higher risk of developing NMSC [ 23 , 24 ]. The incidence of SCC is 250 times higher, and that of BCC is 10 times higher in organ transplant recipients compared to the general population.…”
Section: Discussionmentioning
confidence: 99%